Slavic Mitra. Benevolent and Legal Pole of the Function of Religious Sovereignty in the Slavic Mythology and Epic Slovanský Mitra. Láskavý a právny pól funkcie náboženskej zvrchovanosti v slovanskom mýte a epose - Golema, Martin (Studia mythologica Slavica, 2013)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Dumézil’s discovery of two opposing and complementary faces of the highest power – on the one side legal and priestly, kind, benevolent, shining, near to world and people (“as Mitra”), and on the other side magic, violent, threatening, dark, invisible and distant (“as Varuna”) – gave rise to a lot of research in various Indo-European traditions. Despite the impressive results of such research, the functional place of “Slavic Mitra” is still open. On the following pages we would like to try to indicate whom, where and how to look for this place. Introduced will be several hypotheses with the aim to show that just this functional place probably created an important and irreplaceable part, maybe one of the key pillars of the ancient Slavic model of the world.